Treatment of the refractory angina in the very elderly patients and centenarians - O.A. Yepanchintseva; O.P. Nadorak; Yu.A. Borkhalenko; S.I. Mashkovska; O.J. Zharinov (Кардіохірургія та інтервенційна кардіологія)
In clinical practice, elderly patients are often refractory to the treatment of stable angina, including after revascularization. Clinical case is shown which illustrates problems and possibilities of refractory angina treatment in the elderly patients and centenarians. The main reason for referral to the physician in this case was angina persisting even after repeated endovascular interventions and coronary artery bypass surgery. In addition, despite antiarrhythmic therapy, frequent episodes of atrial fibrillation were observed. Usage of ranolazine in addition to the background treatment provided improvement of various components of the quality of life, apparently by reducing angina and prevention of paroxysmal atrial fibrillation.